A Novel Conceptual Model of e-Participation using Biometrics Technologies. (July 2020) - Yusuf, Muhammad; Muntasa, Arif; Agustiono, Wahyudi; Anamisa, Devie Rosa; Syarief, Mohammad
Abstract: Participation from all relevant stakeholders is important to achieve the goal of every activity successfully. Nowadays, Information and Computer Technologies, for example, Biometrics, Internet of Things (IoT) and Big Data are used to support participation from the relevant stakeholders. Electronic Participation (e-Participation) already utilized broadly to empower people participation in politics, business, government, cultural activities. Moreover, Biometrics has been used broadly for an identification system. Biometrics system identifies physiological instead of behavioral attributes, such as palm veins, iris recognition, face recognition, fingerprint, DNA, palm print, hand geometry, retina, and odor/scent. Therefore, this research would like to collaborate e-Participation and Biometrics fields from the multidisciplinary perspective. Furthermore, the literature reviews show that research collaboration between e-Participation and Biometrics Technologies are still limited. Hence, the objective of this research was to develop a novel conceptual model of e-Participation using Biometrics technologies. This paper contributes by developing a novel conceptual model of biometrics technologies for e-Participation implementation. This research has some implications. For theory development, this research contributes to the novel conceptual model in e-Participation, E-Government, Information Systems, Informatics, Computer Science, Image Processing, and Biometrics fields. For Practice, the novel model could be utilized for practitioners, policy-makers, and other relevant stakeholders for e-Participation implementation using Biometrics Technologies.